Chapter Internet use, feeling of unacceptance and Loneliness: immigrants of first and second generation in Italy - Busetta, Giovanni (Proceedings e report, 2023)
Introduction Internet has become an essential part of our everyday life and several goals can be achieved through it. While part of the literature on the topic found a positive correlation between loneliness and the use of the internet, other authors found a negative relationship between loneliness and internet use. Objective The aim of our analysis is to investigate the difference in the use of the Internet between immigrants of first- and second-generation in Italy. Data & Methods Using the Survey on Social Condition and Integration of Foreign Citizens conducted by Istat in 2011-2012, we want to estimate, through a Probit estimation model, the impact of socio-economic characteristics on the regularity of using the Internet. The dependent variable is "Internauta" (Dummy: 1 if subject use internet every day; 0 otherwise). Among the explanatory variables, we included the perception of the subjects about their integration in the social framework and their feeling, such as loneliness, or the perception of unacceptance. Results Our results show that the probability of being an "Internauta" increases being male and living in the North or Centre of Italy. Moreover, both of the feelings (feels alone and not accepted) are negatively correlated to the probability of being an Internet user both for First- and Second-Generation immigrants. Second-generation immigrants are more likely to use the internet everyday than the First-generation ones (the difference in predicted probability is equal to 11%). This probability decreases to 0.59, if the second-generation immigrant feels unaccepted in the city where he/she lives, and to 0.71 if he/she fells alone. Conclusion We can conclude that new possibilities offered by "web sociability" or, in general, by the use of the Internet, is negatively correlated to the immigrants' dissatisfaction that we identify with the perception of integration and sociability in the offline life (Loneliness and Unacceptance).